Precision Engineering of the Transcription Factor Cre1 in Hypocrea jecorina (Trichoderma reesei) for Efficient Cellulase Production in the Presence of Glucose - Han, Lijuan; Tan, Yinshuang; Ma, Wei; Niu, Kangle; Hou, Shaoli; Guo, Wei; Liu, Yucui; Fang, Xu (Frontiers in Bioengineering and Biotechnology, 2020)
In Trichoderma reesei, carbon catabolite repression (CCR) significantly downregulates the transcription of cellulolytic enzymes, which is usually mediated by the zinc finger protein Cre1. It was found that there is a conserved region at the C-terminus of Cre1/CreA in several cellulase-producing fungi that contains up to three continuous S/T phosphorylation sites. Here, S387, S388, T389, and T390 at the C-terminus of Cre1 in T. reesei were mutated to valine for mimicking an unphosphorylated state, thereby generating the transformants Tr_Cre1S387V, Tr_Cre1S388V, Tr_Cre1T389V, and Tr_Cre1T390V, respectively. Transcription of cel7a in Tr_ Cre1S388V was markedly higher than that of the parent strain when grown in glucose-containing media. Under these conditions, both filter paperase (FPase) and p-nitrophenyl-β-D-cellobioside (pNPCase) activities, as well as soluble proteins from Tr_Cre1S388V were significantly increased by up to 2- to 3-fold compared with that of other transformants and the parent strain. The results suggested that S388 is critical site of phosphorylation for triggering CCR at the terminus of Cre1. To our knowledge, this is the first report demonstrating an improvement of cellulase production in T. reesei under CCR by mimicking dephosphorylation at the C-terminus of Cre1. Taken together, we developed a precision engineering strategy based on the modification of phosphorylation sites of Cre1 transcription factor to enhance the production of cellulase in T. reesei under CCR.